Multiplexní detekce psychotropních látek v laterálním toku na membráně s nanočásticemi zlata - Ďurčiová, Barbora; Zolal, Aram; Syslová, Kamila; Kačer, Petr (Chemické listy, 2016)
One step multiple test line lateral flow immunoassay was designed in a competitive format for the detection of drugs of abuse (namely morphine, 3,4-methylen-dioxymethamphetamine, phenycyclidine and amphetamine) from oral fluids. For the labeling of antibodies, gold nanoparticles produced by the Turkevich method were used. It was found that saliva contains mucin glycoproteins which cause non-specific interactions on test lines. These undesirable interactions can be influenced by higher pH, higher buffer capacity, and a choice of suitable detergent for the sample pad buffer in combination with suitable sample pad material. Optimized sample pad buffer contained 100 mM Tris and 0.5% sodium deoxycholate to yield pH 9.0. Screening of all the materials (mainly sample pad, conjugate pad) was performed and Fusion 5 was selected in order to develop rapid test able to provide results within 10 minutes. The other key advantage of this format of the test, as compared to other immunoassays, is its low cost and simplicity requiring no sample or reagent preparation and no photodetector for its measurement.
Keywords: Immunochemistry; Mucins; Gold; Substance Abuse Detection; Saliva; kyselina deoxycholová; Nanoparticles; nanočástice; psychotropní léky; muciny; odběr biologického vzorku; zlato; Psychotropic Drugs; Deoxycholic Acid; imunochemie; chromatografie afinitní; lidé; Humans; Specimen Handling; odhalování abúzu drog; sliny; Chromatography, Affinity